Factors for Selecting Honda Matic Motorcycles In Medan City With Analitycal Hierarchy Process (AHP) Method - Wiranto, Andri (UIN Sumatera Utara, 2021)
The city of Medan is the center of government, trade, education and so on in the North Sumatra region. The high mobility in the city of Medan makes the transportation system very important. The problem of transportation in the city of Medan is also a very complex problem, especially the increasing dependence on private vehicles, both cars and motorbikes. And this causes congestion to be higher in the city of Medan and has become a common thing. Along with the development of automatic motorcycle transportation, which is increasing, both in terms of motorcycle design criteria, vehicle performance, and fuel economy used. Therefore, not a few consumers have difficulty in choosing an automatic twowheeled vehicle that suits their needs. The purpose of this study is to analyze the factors that influence the selection of Honda matic motorcycles in Medan using the AHP (analitycal hierarchy process) method. The AHP method is a decision support system aimed at assisting consumers in the process of selecting a Honda matic motorcycle to be purchased according to their needs